Dimensions, components and metrics of energy security: Review and synthesis - John A. Paravantis (SPOUDAI - Journal of Economics and Business, 2019)
Size, technological scale and monetary investment have kept energy connected to geopolitical contention. With the shale revolution putting peak oil concerns aside and the global rearrangement of energy consumer and producer roles, the emergence of China and India have focused attention on energy security. This paper reviews tens of dimensions, components and metrics that may be used to define energy security, and the methods that may be used to calculate an energy security index. The 4As (availability, affordability, accessibility and acceptability), the five Ss (surety, survivability, supply, sufficiency and sustainability) and other similar approaches are discussed with corresponding metrics. A concise and inclusive novel energy security index is synthesized, with seven no overlapping dimensions: physical availability, technology development, economic affordability, social accessibility, governance, unconventional threats, and natural environment. Since the dimensions of an energy security index are not perceived as having equal importance by different economic actors or the research literature, a small group of energy, economics, technology, geopolitics and environment experts was asked to rate their importance of the seven dimensions of the proposed index. Physical availability was rated as the most important, and natural environment as the least important dimension. In forthcoming research, this energy security index will be combined with the appropriate qualitative methods to reframe geopolitical problems.
Keywords: Q34; Q35; 330; Energy security; energy security index; expert interviews; geopolitics